Selective Limbic Blood–Brain Barrier Breakdown in a Feline Model of Limbic Encephalitis with LGI1 Antibodies - Tröscher, Anna R.; Klang, Andrea; French, Maria; Quemada-Garrido, Lucía; Kneissl, Sibylle Maria; Bien, Christian G.; Pákozdy, Ákos; Bauer, Jan (Frontiers in Immunology, 2017)
Human leucine-rich glioma-inactivated protein 1 encephalitis (LGI1) is an autoimmune limbic encephalitis in which serum and cerebrospinal fluid contain antibodies targeting LGI1, a protein of the voltage gated potassium channel (VGKC) complex. Recently, we showed that a feline model of limbic encephalitis with LGI1 antibodies, called feline complex partial seizures with orofacial involvement (FEPSO), is highly comparable to human LGI1 encephalitis. In human LGI1 encephalitis, neuropathological investigations are difficult because very little material is available. Taking advantage of this natural animal model to study pathological mechanisms will therefore contribute to a better understanding of its human counterpart. Here, we present a brain-wide histopathological analysis of FEPSO. We discovered that blood-brain-barrier leakage was present not only in all regions of the hippocampus but also in other limbic structures such as the subiculum, amygdala and piriform lobe. However, in other regions, such as the cerebellum, no leakage was observed. In addition, this brain-region specific immunoglobulin leakage was associated with the breakdown of endothelial tight junctions. Brain areas affected by blood-brain-barrier dysfunction also revealed immunoglobulin and complement deposition as well as neuronal cell death. These neuropathological findings were supported by magnetic resonance imaging (MRI) showing signal and volume increase in the amygdala and the piriform lobe. Importantly, we could show that blood-brain-barrier disturbance in LGI1 encephalitis does not depend on T cell infiltrates, which were present brain-wide. This finding points towards another, so far unknown, mechanism of opening the blood-brain barrier. The limbic predilection sites of immunoglobulin antibody leakage into the brain may explain why most patients with LGI1 antibodies have a limbic phenotype even though LGI1, the target protein, is ubiquitously distributed across the central nervous system.